Membangun Sistem Rekrutmen Calon Pegawai Negeri Sipil Pada Era Otonomi Daerah - Iqbal, Mahathir Muhammad (ARISTO, 2017)
The concept of decentralization which manifests the concept of local autonomy has implications for efforts to strengthen regional governance based on local potential, including strengthening resource management apparatus is characterized by the process and implementation of personnel management started from procurement personnel consisting of; planning, formation, recruitment and selection, development, promotion, remuneration, discipline, and dismissal or retirement. Procedures and implementation of recruitment candidates for Civil Servants (CPNS) from internal sources (Workers Honorary) and from external sources (the general public) or a common path, and potentially very susceptible to spoil the practice of system and Nepo system. One of the efforts that must be made to minimize all forms of deviation in the framework of the process of recruitment and implementation is to implement a merit system, as the antithesis of giving jobs on the basis of race, ethnicity, religion, political award, gender discrimination, personal favoritism, or the selection of equipment valid.